A study of a strain of albino mice with regard to suitabilty for investigations of the role of the adrenal cortex in mammary gland growth : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in the University of New Zealand - Munford, R E (Massey University, 1956)
The experiments reported in this thesis were carried out in the hope that they might assist in the clarification of the role of the endocrine system in the regulation of mammary gland development. A large part of the work was concerned with the elucidation of the general effects of adrenal insufficiency in mice, and with the maintenance of adrenalectomised mice by the injection of cortisol acetate. It is hoped that the results obtained with these mice will be of some assistance in future studies of the endocrine control of the growth of the mammary glands in mice, where it is dersired to exclude any influence mediated by, or originating from the animal's own adrenal cortex. This study w_as prompted by Dr. D.S. Flux, to whom the author is indebted for guidance, encouragement, and patient instruction. The advice of Professor I.L. Campbell, in whose department the work was carried out, and the assistance of Mr D.J. Myers are gratefully acknowledged. The author also wishes to thank the staff of the College Library for their considerable efforts in obtaining a large number of .journals on loan from other institutions, and Mr. K.A. Rose for his work in connection with the reproduction of the illustrations. Thanks are also due to the following for gifts of material to Dr. D.S. Flux: Organon Ltd., England for oestrone (through the courtesy of Mr. G.B. Davis of The Dental and Medical Supply Co. Ltd.) A.M. Satterthwaite and Co. Ltd. for cortisol (through the courtesy of Mr. F.A. Hacking). [From Preface]
Keywords: Adrenal cortex; Physiology; Mice; Mammary glands; Growth